(untitled) - Fox, Stuart Ira (Boston, 2006)
Human Physiology is intended for the one-semester Human Physiology course often taken by allied health and other biology students. The beginning chapters introduce basic chemical and biological concepts to provide students with the framework they need to comprehend physiological principles. The chapters that follow promote conceptual understanding rather than rote memorization of facts. Health applications are included throughout to heighten interest, deepen understanding of physiological concepts, and help students relate the material to their individual career goals. Every effort has been made to help students integrate related concepts, and understand the relationships between anatomical structures and their functions.
Keywords: Human physiology,Sinh lý học người